Corn productivity in different fertilization managements with vinasse and potassium chloride - Sousa, Juliana Pereira de; Cabral Filho, Fernando Rodrigues; Andrade, Christiano Lima Lobo de; Teixeira, Marconi Batista; Alves, Daniely Karen Matias; Silva, Nelmício Furtado da (Brazilian Journal of Science, 2023)
Corn (Zea mays L.) is one of the most important cereals in the world. This crop has a high requirement for nutrients, such as potassium (K). This nutrient can be obtained from alternative sources such as vinasse for the corn crop, representing positive agronomic, economic, and environmental effects. The objective of this work was to evaluate use of vinasse and potassium chloride, in fertirrigation in the hybrid AS1820 PRO3 maize crop at different doses. The experiment was carried out in the experimental area of the IF Goiano, Rio Verde, Goiás, Brazil, harvest 2021/22. The variables studied were number of ears per plant, number of grains per row, number of grains per plant, diameter and length of ears, mass of grains per plant, productivity, and number of bags per grain. We verified that there was no significant difference (positive effects) for the data of the variables analyzed in this experiment. It was concluded that the corn hybrid AS1820 PRO3 did not have a positive effect on the variables analyzed with vinasse and potassium chloride fertirrigation in our study, requiring new complementary experiments.